Temporomandibular Disorders and Parafunctional Habits in Children and Adolescence: A Review - B. Seraj; R. Ahmadi; M. Mirkarimi; S. Ghadimi; M. Beheshti (Tehran University of Medical Sciences, 2009)
The aim of this study is to review the existing literature about temporomandibular disorders (TMD) and parafunctional habits (bruxism) and their relationship in children and adolescents, which is still controversial. TMD is a collective term used to identify a group of musculoskeletal conditions of the temporomandibular region. Bruxism defined as the habitual nonfunctional forceful contact between occlusal tooth surfaces. Some studies have linked oral parafunctional habits to TMD, whereas others did not observe this relationship. The role of bruxism -as is currently described- can be considered a controversial and unresolved issue. Taking all evidence together,the authors suggest that there is not any clear relationship between bruxism and TMD.